On the issue of reforestation methods (using a substrate for planting seedlings) - Prokhorova Nadezhda (BIO Web of Conferences)
The problem of forest conservation is currently the most acute. In the current extreme conditions due to global climate change, reforestation and protection of forest resources require special attention, as well as new methods and approaches to solving emerging problems in this direction. Wildfires destroy huge forests, this is a step towards an environmental disaster, since the functions of the forest are not only an "oxygen production factory", but also the protection and protection of water resources and soil. In this regard, great attention is paid to afforestation, various methods of growing tree species are proposed and used. Foresters are studying new progressive technologies of reforestation, using various substrates that contribute to the production of high-quality tree plantations. The article presents an analysis of data obtained during research on the cultivation of pine seedlings (Latin) using a substrate based on waste from the woodworking industry. The research was carried out as part of the research work of students and postgraduates of the Forestry Engineering University. The research results allow us to conclude that it is advisable to use a substrate, which will allow not only to preserve living green spaces, but also to effectively use waste from the woodworking industry.